Rola i znaczenie pamięci o KL Auschwitz-Birkenau w edukacji historycznej Polaków i Niemców. Konfrontacja pamięci indywidualnej z doświadczeniem miejsca - Praga, Agnieszka (Załącznik Kulturoznawczy, 2023)
How is the memory of the Holocaust and Auschwitz seen today among young Poles and Germans, is it different from that of the past? What are the differences in the memory space and education about the Holocaust between the two countries, and what do they have in common? The article is based on three pillars, and what served as foundations for them was a survey conducted with Polish and German youth in late April and May 2013, immediately after their visit to the Auschwitz-Birkenau. The first part concerns the individual and family memory of young people from Poland and Germany, who came to the Memorial and Museum of Auschwitz-Birkenau (MMA-B); there are also issues related to the intergenerational transmission of war fate of the relatives. The second pillar takes on teaching about the Holocaust at school and the evaluation of historical education from the student’s point of view. There are presented the opinions of many historians, teachers and educators struggling with the effects of the reform of history teaching. The third and most extensive part of the article presents the issues related to historical education in the memorial site and young people confronting their past experience, knowledge, notions with the authenticity of MMA-B. Fundamental questions has been raised about the sense of maintaining authenticity of the memorial site and the reason that makes the memory of the Holocaust such an important task for future generations.